REVIEW PAPERRole of Periodontal Infection in Cardiovascular Disease: A Current Perspective - Shanker, Jayashree; Kakkar, Vijay V. (Archives of Medical Science, 2009)
Oral pathogens play a causal role in Cardiovascular Disease (CVD) that is largely driven by inflammation and host immune response. Clinico-epidemiological and animal studies provide a strong link between periodontal disease (PD) and CVD, both of which are highly prevalent, complex disease processes with common risk factors. Genes involved in inflammation, matrix degeneration and immune response have been implicated in the initiation and progression of both diseases. Recent studies have promoted the discovery of novel pathways and lead molecules thus providing opportunities for developing effective vaccine candidates to control disease progression. Following periodontal therapy, studies have shown reduction in the levels of pro-inflammatory cytokines and acute phase reactants, enhancement of endothelial function and lowered risk for future cardiovascular events. The above parallel provides a small yet important handle by which improvement in oral health can open up wider avenues for the overall betterment of systemic health.